OPTIMIZATION OF ONLINE STATEMENT OF POLICE REPORT SERVICES BY INTELIGENCE AND SECURITY UNIT TO IMPROVE COMMUNITY SERVICES IN THE JURISDICTION OF THE SALATIGA POLICE - ANDI KHAERIN PANDAWA SATRIA (Advances in Police Science Research Journal, 2022)
This research is based on the innovation of the Indonesian National Police in serving the community, in the form of service innovation in the form of online Statement of Police Report services. However, the online SKCK applicant rate is lower than the manual Statement of Police Report. This is because there are still many people who do not know about the online SKCK and understand how to use it. Therefore, a study was conducted that aims to find out how to optimize online Statement of Police Report services at the Salatiga Police Station, as well as what are the inhibiting factors for the implementation of online Statement of Police Report services at the Salatiga Police Station. This research uses the concept of optimization, the concept of public service, and the online Statement of Police Report concept and uses organizational resource theory and management theory as an analytical knife. This approach uses a qualitative approach with the type of descriptive research. The data sources used are primary data sources in the form of interviews, and secondary data sources in the form of documents, books and research related to this research. Data collection techniques in this study used observation, interviews and document review. The data analysis techniques used are data collection, data reduction, data presentation and conclusion drawing Research conducted at the Salatiga Police Station resulted in the finding that online Statement of Police Report aims to make it easier for applicants and officers to make Statement of Police Report, but the number of online Statement of Police Report applicants at the Salatiga Police Station is still less compared to manual. The inhibiting factors in carrying out these services are caused by internal factors such as the absence of personnel who have done training, the presence of personnel who do not receive honoraria for service implementers, as well as equipment received from the center that cannot operate optimally and external factors that come from the community. itself. With this, the Salatiga Police Intelligence Unit has not been able to provide services in accordance with the concept of public service. The author's suggestion in this study is to eliminate the inhibiting factors for online Statement of Police Report services and increase the socialization carried out to the Salatiga community so that people use online Statement of Police Report.